Combined Effect of Soil Particle Size Fractions and Engineered Nanoparticles on Phosphate Sorption Processes in Volcanic Soils Evaluated by Elovich and Langmuir–Freundlich Models - Arancibia-Miranda, N; Arancibia-Miranda, N; Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Springer Science and Business Media Deutschland GmbH, 2022)
Engineered nanoparticles (ENPs) released into the environment can affect phosphate (Pi) availability in soils. In this study, we evaluated the effect of silver (Ag) or copper (Cu) ENPs (3 and 5%, w/w) on Pi sorption processes in soil particle size fractions. The 2000–32 μm, 32–2 μm, and < 2 μm fractions were obtained from an agricultural volcanic soil by wet-sieving and sedimentation methods. The Elovich kinetic and Langmuir–Freundlich (L-F) isotherm models were used to describe the adsorption data obtained from batch experiments. The initial adsorption rate (α) was determined from the Elovich model to be 105% higher for the 2000–32 μm fraction and 203% higher for the 32–2 μm fraction than for the < 2 μm fraction (671 mmol kg−1 min−1). Meanwhile, with both doses of Cu ENPs, the α values are increased for the soil size fractions, resulting in the formation of adsorption sites for Pi. However, with Ag ENPs, the α values are both increased and decreased for the different soil fractions; therefore, they can block or generate adsorption sites. The maximum adsorption capacity (qmax) was determined from the L-F model to be 17% higher for the 32–2 μm fraction and 47% higher for the < 2 μm fraction compared to that for the 2000–32 μm fraction (180 mmol kg−1). With both ENPs, the qmax values are found to be between 1.1 and 1.9 times higher with respect to the 2000–32 μm fraction without ENPs. In the absence of ENPs, the highest Pi desorption was found in the 32–2 μm fraction followed by 2000–32 μm fraction, and finally < 2 μm fraction. Moreover, the Pi desorption decreased for soil size fractions with increasing Ag or Cu ENPs content, which was found to be more pronounced in the 32–2 μm fraction in the presence of Cu ENPs. The presence of Ag and Cu ENPs increases Pi retention in soil size fractions, which can decrease soil fertility. Thus, future studies are recommended to find out the critical amounts of ENPs, which may favor Pi retention without any negative effects on agricultural soils. © 2022, The Author(s) under exclusive licence to Sociedad Chilena de la Ciencia del Suelo.